2015
DOI: 10.1186/s12864-015-2032-0
|View full text |Cite
|
Sign up to set email alerts
|

The rumen microbial metagenome associated with high methane production in cattle

Abstract: BackgroundMethane represents 16 % of total anthropogenic greenhouse gas emissions. It has been estimated that ruminant livestock produce ca. 29 % of this methane. As individual animals produce consistently different quantities of methane, understanding the basis for these differences may lead to new opportunities for mitigating ruminal methane emissions. Metagenomics is a powerful new tool for understanding the composition and function of complex microbial communities. Here we have applied metagenomics to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
308
7
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(352 citation statements)
references
References 67 publications
30
308
7
7
Order By: Relevance
“…The relationship between rumen methanogen abundance and methanogenesis is less clear when changes in enteric CH 4 emissions are modulated by diet or are a consequence of selecting phenotypes related to feed efficiency or MeY. Whereas in some reports, significant positive relationships were identified (Aguinaga Casañas et al, 2015;Arndt et al, 2015;Sun et al, 2015;Wallace et al, 2015), in many others, the concentration of methanogens was unrelated to methanogenesis (e.g., Morgavi et al, 2012;Kittelmann et al, 2014;Shi et al, 2014;Bouchard et al, 2015). Bouchard et al (2015) even reported a reduction in methanogens without a significant decrease in MeP for steers fed sainfoin silage.…”
Section: Rumen Function Metabolites and Microbiomementioning
confidence: 97%
See 1 more Smart Citation
“…The relationship between rumen methanogen abundance and methanogenesis is less clear when changes in enteric CH 4 emissions are modulated by diet or are a consequence of selecting phenotypes related to feed efficiency or MeY. Whereas in some reports, significant positive relationships were identified (Aguinaga Casañas et al, 2015;Arndt et al, 2015;Sun et al, 2015;Wallace et al, 2015), in many others, the concentration of methanogens was unrelated to methanogenesis (e.g., Morgavi et al, 2012;Kittelmann et al, 2014;Shi et al, 2014;Bouchard et al, 2015). Bouchard et al (2015) even reported a reduction in methanogens without a significant decrease in MeP for steers fed sainfoin silage.…”
Section: Rumen Function Metabolites and Microbiomementioning
confidence: 97%
“…Some methodological and experimental differences might explain some of these apparent contradictions, such as the type of gene target and primers used for nucleic acid amplification. Effects are seen most clearly when the difference in MeP between groups of animals is large; for example, Wallace et al (2015) used treatments that generated a 1.9-fold difference in CH 4 emissions. Roehe et al (2016) observed that the ranking of sire groups for CH 4 emissions measured with respiration chambers was the same as that for ranking on archaea:bacteria ratio, providing further evidence that host control of archaeal abundance contributes to genetic variation in CH 4 emissions, at least in some circumstances.…”
Section: Rumen Function Metabolites and Microbiomementioning
confidence: 99%
“…No strong associations were found between the most abundant rumen bacteria and archaea (~3% of microbes that are mostly autotrophic methanogens). However, Wallace et al (2015) reported that the abundance of archaeal genes in ruminal digesta correlated strongly with differing methane emissions from individual animals. Lower emissions were accompanied by higher Succinovibrionaceae abundance and changes in acetate and hydrogen production leading to less methanogenesis.…”
Section: Country and Other Effectsmentioning
confidence: 99%
“…spp. in the "high" emitters (Wallace et al, 2015). Such findings suggest that gaseous hydrogen formation by the microbiota can affect both the ecology and quantity of methanogenic archaea .…”
Section: Chapter 4 Variations In Methanobrevibacter and Methanosphaermentioning
confidence: 82%
“…in the "high" emitters, while changes in the bacterial population favouring the succinate-producers like Succinivibrionaceae were found in the "low" emitting animals. Furthermore, these variations in metagenomic data between the "high" and "low" emitters have been proposed as biomarkers for animal selection and breeding strategies that seek to reduce methane emissions and/or improve feed efficiency (Wallace et al, 2015). Indeed, it would seem that the alterations in methanogen profiles observed among animals stratified by their methane emissions involves genotype x environment interactions that affect rumen fermentation and gaseous hydrogen formation .…”
Section: Methane Emissions Methanogenic Archaea and The Ruminant Hostmentioning
confidence: 99%